KEDUDUKAN HUKUM DOKTER YANG MENOLAK SEBAGAI EKSEKUTOR KEBIRI KIMIA - Jihan Nika Rohfatul Adhana; Hari Soeskandi (Gapenas Publisher, 2022)
He is behind the arguments against the imposition of chemical castration sanctions on perpetrators of pedophilia crimes, which are considered serious crimes due to the high number of victims and cause psychological trauma to children and harm. Therefore, the Indonesian government took this issue seriously and enacted Law No. 17 of 2016, which provides additional punishments for pedophile criminals in the form of chemical castration. This additional punishment is a cause of state concern for the children of the nation and for generations to come. This creates a dilemma, however, for doctors who have their own profession and experience in the medical field, who are worthy of being the perpetrators of chemical castration on criminals. The President of the Indonesian Medical Association (IDI) said he would reject use of doctors as enforcers of chemical castration sanctions. The medical profession is involved in the process of punishment through chemical castration against ethical rules or (oath) and the Medical Practices Act No. 29 of 2004, which they use as a guide to carry out all their actions. The author focuses on the legal status of a doctor who refused chemical castration. The article uses the method of legal research with a legal approach, a conceptual approach. It is against the Code of Ethics or (Oath) and the Law on Medical Practices No. The author focuses on the legal status of a doctor who refused chemical castration. The article uses the method of legal research with a legal approach, a conceptual approach. The involvement of the medical profession in the process of punishment through chemical castration is against the Code of Ethics or (Oath) and e Law No. 29 of Medical Practice 2004, which they use as a guide in carrying out all their duties. movements The author focuses on the legal status of a doctor who refused chemical castration. The article uses the method of legal research with a legal approach, a conceptual approach. The article uses the method of legal research with a legal approach, a conceptual approach. The involvement of the medical profession in the process of punishment through chemical castration is against the Code of Ethics or (Oath) and e Law No. 29 of Medical Practice 2004, which they use as a guide in carrying out all their duties. movements The author focuses on the legal status of a doctor who refused chemical castration. Article, he uses a legal research method with a legal, conceptual approach. The article uses the method of legal research with a legal approach, a conceptual approach. they used it as a guide for all actions. The author focuses on the legal status of a doctor who refused chemical castration. The article uses the method of legal research with a legal approach, a conceptual approach. they used it as a guide for all actions.The legal position of a doctor who refuses chemical castration is clear here. There is no doubt that doctors will be an assistant prosecutor's team in the execution of sexual crimes against children in the form of chemical castration sanctions, ordered by the Mojokerto court to commit sexual offenses against Mohammed. Brother Aris (MA), which has permanent legal force (ink box) and is no longer rejected by doctors due to violations of the Medical Ethics Code or the Medical Practices Act No. Because the Code of Ethics is not a law, the Code of Ethics is not a legislative act, but a rule in medicine that is usually only accepted by certain groups if it was established by the Indonesian Medical Association (IDI). As, ethical rules must comply with the law in accordance with the legislative hierarchy. modeThe author uses, modifies, or withdraws the principle of preemption Lex Posteriori Derogat Legi Priori when comparing or analyzing the laws to which physicians will be subject or to be used as reference material, acknowledging that the conflict of old law concerning with the same subject. . It was published Law of Medical Practice No. 29 of 2004 dated October 6, 2004 and came into force on October 6, 2005. In the meantime, the Child Protection Law No. 17 dated 2016 and came into force on 9 November 2016. here the author concludes that doctors must comply with the new law according to the principle of Lex Posteriori Derogat Legi Priori. With such a strong foundation, there is no need to put doctors in a dilemma to become a chemical castration